2021
DOI: 10.1007/s10902-021-00443-9
|View full text |Cite
|
Sign up to set email alerts
|

Can Money Buy Happiness? Subjective Wellbeing and Its Relationship with Income, Relative Income, Monetary and Non-monetary Poverty in Bangladesh

Abstract: This paper presents an empirical analysis of the importance of income, relative income, monetary and non-monetary poverty for individual wellbeing or happiness in rural Bangladesh. The study is the first estimate of a wellbeing function for Bangladesh using nationally representative micro-panel data. Employing a linear panel model with individual random effects and a large set of control variables like education, working status and disability, we found a strong and positive relationship between wellbeing and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…For example, in his study of neighbourhood satisfaction, Mouratidis (2020) found that the linear regression models returned R-squares of between 0.048 and 0.161. Similar results were also obtained by studies on both the specific aspect of satisfaction (i.e., residential satisfaction in Ren and Folmer, 2017) and general subjective wellbeing (Tauseef, 2021).…”
Section: Empirical Findings and Discussionsupporting
confidence: 85%
“…For example, in his study of neighbourhood satisfaction, Mouratidis (2020) found that the linear regression models returned R-squares of between 0.048 and 0.161. Similar results were also obtained by studies on both the specific aspect of satisfaction (i.e., residential satisfaction in Ren and Folmer, 2017) and general subjective wellbeing (Tauseef, 2021).…”
Section: Empirical Findings and Discussionsupporting
confidence: 85%
“…Since the emergence of the Easterlin Paradox, scholars have tried to crack the happiness code from different perspectives [ 14 ]. From absolute income to relative income to income inequality, income has been an important focus of scholarly attention [ 5 , [15] , [16] , [17] ]. In addition, there have been a variety of studies on the relationship between happiness and socio-demographic factors, such as age, gender, education, marital status, health status, housing status and religious beliefs [ 6 , [18] , [19] , [20] ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The essence of the rural welfare effect requires the government to meet the basic needs of the rural population through institutionalized social security based on legislation, improve rural poverty, achieve universal welfare, and provide individual farmers with basic livelihood welfare such as basic employment, basic medical care, basic pension and so on [ 17 ]. Recently, farmers' psychological satisfaction and happiness are believed to be the most critical factors of the welfare effect [ 18 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%